Combination Effect Between Lead and Salinity on Anatomical Structure of Date Palm Phoenix dactylifera L. Seedlings - Al-Aradi, Haleemah J.; Al-Najjar, Mohammed A.; Awad, Khairullah M.; Abass, Mohammed H. (AGRIVITA, Journal of Agricultural Science, 2020)
The study was conducted to evaluate the effect of lead (Pb) stress alone or in combination with salinity on the anatomical structure of roots and leaves of Date palm seedlings. Pb was added to soil at 100, 300 and 600 mg/kg concentrations as a pure aqueous solution or mixed with saline solution at 200 mM. Compared with the control, the microscopic study of root tissues showed that all treatments caused a significant increase in the thickness of epidermis, endodermis and pericycle, whereas the cortex thickness and diameters of the vascular cylinder, protoxylem and metaxylem decreased significantly. However, only the phloem diameter was affected significantly by 600 mg/kg Pb with or without salinity. Compared with the control, results on leaf tissues revealed that treatment with 300 and 600 mg/kg Pb alone or in combination with salinity led to a significant increase in the thickness of cuticle layer, upper epidermis and lower epidermis. Results also showed a significant increase in the diameter of tannin and palisade cells when treated with 100 mg/kg Pb with or without salinity. Small vascular bundle diameter decreased significantly in seedlings exposed to Pb at all examined concentrations with or without salinity.